Additively manufactured functional cylindrical metastructures with controllability in both thermal expansion and Poisson’s ratio - Ye Zhou; Qidong Yang; Jiaxin Chen; Rongzheng Huang; Hao Zhou; Zhonggang Wang; Kai Wei (Virtual and Physical Prototyping)
Multi-functional cylindrical metastructures, integrating the controllability in both coefficient of thermal expansion (CTE) and Poisson’s ratio (PR), provide promising alternatives for both temperature- and mechanical-sensitive components used in advanced industrial equipment. However, the sophisticated cellular and cylindrical geometries still give rise to an enormous challenge in fabrication process, and hence the controllability in both CTE and PR is still not practically realised. Herein, a series of new multi-functional cylindrical metastructures are designed by a curling strategy to exclusively integrate the controllability in both CTE and PR. Besides, the laser powder bed fusion (PBF-LB) process is originally developed to fabricate the cylindrical metastructures by using Invar 36 alloy as the constituent, and the exceptional manufacturing quality is realised by the customised PBF-LB process. In addition, the cylindrical metastructures effectively inherit the Invar effect of the constituent, and the controllable low CTEs, in the range of 1.80∼1.90 ppm/°C, are first experimentally achieved. Furthermore, the PR is also flexibly and experimentally controlled in the range of -0.62∼+0.43. These cylindrical metastructures open the avenue towards the cooperative design and additive manufacturing of multi-functional metastructures, which integrate lightweight, preferred mechanical performances or functions, motivated by the urgent requirement from advanced industrial equipment.